Rheumatological evaluation of patients with interstitial lung disease. (2nd January 2022) - Ottaviani, S; Khaleche, S; Borie, R; Debray, M-P; Dieudé, P; Crestani, B
Abstract : Objective : Interstitial lung disease (ILD) is a common feature of connective tissue disease (CTD). The diagnosis of CTD-ILD can be challenging and is important for therapeutic decisions. In this study, we aimed to determine whether a systematic rheumatological assessment could help pulmonologists in the diagnosis and care of ILD patients. Method : We conducted an observational single-centre study of patients with ILD. All patients underwent standardized pulmonary and rheumatological evaluations, including clinical evaluation (pulmonary symptoms and musculoskeletal signs), immunological screening, chest high-resolution computed tomography, pulmonary function tests, and ultrasonography (US) of joints and major salivary glands. Results : We included 100 consecutive ILD patients (47% women, mean ± sd age 67 ± 14 years); 15 patients already had CTD. The main extrapulmonary symptoms were joint pain (n = 52), joint swelling (n = 26), and sicca syndrome (n = 33). US of joints revealed synovitis, bone erosion, and tenosynovitis in 37, 17, and 13 patients, respectively. US of major salivary glands detected features associated with Sjögren's syndrome in 13 patients. After rheumatological evaluation, CTD-ILD was confidently diagnosed in 39 patients; diseases were mainly rheumatoid arthritis (n = 20), primary Sjögren's syndrome (n = 17), and inflammatory myopathies (n = 7). The diagnosis of CTD-ILD was associated with the presence of musculoskeletal symptoms and immunological and US abnormalities. The CTD diagnosis led to a therapeutic change in 21 patients. Conclusion : Our findings suggest that musculoskeletal symptoms are frequent in ILD patients, which supports multidisciplinary management, involving the rheumatologist, for evaluating patients with ILD.